A multi-isotopic study of the groundwaters from the Lower Triassic Sandstones aquifer of northeastern France: Groundwater origin, mixing and flowing velocity. (August 2021) - Innocent, Christophe; Kloppmann, Wolfram; Millot, Romain; Vaute, Laurent
Abstract: Water samples from the Lower Triassic Sandstones aquifer (LTS), plus two waters from the overlying Muschelkalk aquifer and one water from the Dogger limestones are the matter of this geochemical and multi-isotopic study (δ 18 O, δD, δ 34 S, 87 Sr/ 86 Sr, δ 11 B, δ 7 Li). In addition, C isotopic compositions and 14 C activities were measured. This study aimed at constraining the origin of waters, water/rock interaction processes, and groundwater flow and residence times within their aquifer. LTS groundwaters have a meteoric origin, some of them recording the very minor contribution of Triassic brines from the deepest aquifer of the Paris Basin, especially at the west end of the LTS aquifer. The two waters from the Muschelkalk aquifer (one of them being the famous Great Source® of Contrexéville), as well as the Dogger water also originate ultimately from meteoric waters. Boron isotopes emphasize in some waters, especially South of the Bray-Vittel Fault (BVF), interaction processes between fluids and clayey lithologies that are present in some places in the aquifer, apart from the aquicludes. Sr and Li isotopic signatures measured in some LTS waters, especially in the Vittel area South of the fault indicate that leakage processes probably occur between the Muschelkalk aquifer and the LTS aquifer. Calculated 14 C residence times indicate flowing velocities in the order of 1–3 m/year, depending on leakage rates. Velocities are found to decrease northwestwards, towards the center of the Paris Basin. Geochemical differences between waters sampled North and South of the BVF indicate that this major fault constrains the circulation of groundwaters in this area. Highlights: This paper reports on groundwaters from northeastern France. Groundwaters from the Buntsanstein and Muschelkalk aquifers have a meteoric origin. Sr and Li isotopes indicate leakage processes between these two aquifers. Groundwater circulation in this area is constrained by the Bray – Vittel Fault. Calculated  14 C residence times indicate flowing velocities of 1 to 3 m/y.